191k views
3 votes
Solve for x: −3|2x + 6| = −12

User Samirahmed
by
6.8k points

2 Answers

3 votes
-3 | 2x + 6 | = -12
| 2x + 6 | = -12/-3
| 2x + 6 | = 4

2x + 6 = 4 -(2x + 6) = 4
2x = 4 - 6 -2x - 6 = 4
2x = -2 -2x = 4 + 6
x = -1 -2x = 10
x = -5

solution is : x = -1 or x = -5
User Mueslo
by
5.1k points
5 votes
−3|2x + 6| = −12

−3(2x + 6) = −12
-6x - 18 = -12
-6x = -12 +18
-6x = 6
x=-1

−3 [-(2x + 6)] = −12
−3 (-2x - 6) = −12
6x +18 = -12
6x = -12 -18
6x = -30
x=-5
answer: x= -5 and x = -1


User Jaye Renzo Montejo
by
5.9k points